- #1

Johnahh

- 88

- 0

So i am having a slight problem deriving this equation.

there is a simple way which is

v=u+at -> t = v-u/a

s = (v+u)t/2

so s = (v+u)*(v-u)/2a

2as = (v+u)(v-u)

2as = v

v

but i am having trouble understanding this way

V

V

V

V

i know that s=u+u+at/2*t i.e s=u+v/2*t

so with V

you can remove 2a as V

this leaves a*a t*t u+u+t+t

then remove u+u+a+t+t for s=u+u+at/2*t

then i am left with a and t*t and i don't know what to do with it.

please help this is really grinding on me that i can't derive this, very annoying!

there is a simple way which is

v=u+at -> t = v-u/a

s = (v+u)t/2

so s = (v+u)*(v-u)/2a

2as = (v+u)(v-u)

2as = v

^{2}-u^{2}v

^{2}=u^{2}+2asbut i am having trouble understanding this way

V

^{2}=(u+at)^{2}V

^{2}=(u+at)(u+at)V

^{2}=u^{2}+a^{2}t^{2}+2uat - i can't understand how you get from this to;V

^{2}=u^{2}+2a(ut+0.5at^{2})i know that s=u+u+at/2*t i.e s=u+v/2*t

so with V

^{2}=u^{2}+a^{2}t^{2}+2uat you have a*a t*t u+u+a+a+t+tyou can remove 2a as V

^{2}=u^{2}+2a(ut+0.5at^{2})this leaves a*a t*t u+u+t+t

then remove u+u+a+t+t for s=u+u+at/2*t

then i am left with a and t*t and i don't know what to do with it.

please help this is really grinding on me that i can't derive this, very annoying!

Last edited: